PENGARUH PAJAK DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH DENGAN JUMLAH PENDUDUK SEBAGAI VARIABEL MODERASI: Studi empiris pada Kota Tangerang Selatan - Salfani Tai; Dila Angraini (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2022)
This study aims to analyze simultaneously and partially the effect of local taxes and levies on the original income of the south Tangerang City area for the 2011-2020 period with moderation variables, namely the number of residents. The type of data used is quantitative data. The data used is primary data obtained from BPS South Tangerang City and DGT. Ministry of Finance. The population in this study is the report on the realization of the South Tangerang city budget for the 2011-2020 period at the Central Statistics Agency of South Tangerang Province using the census sampling method, while the sample from this study is a report on the realization of the South Tangerang city BUDGET for the 2011-2020 period. From the results of the study, it can be concluded that all independent variables, namely regional taxes and regional levies, simultaneously affect local original income. partially local taxes affect local revenues, local levies affect local revenues, populations moderate the relationship of local taxes to local revenues and populations do not moderate the relationship of local levies to local revenues